The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.jpubeco.2005.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Public health investments and the infant mortality gap: Evidence from federal sanitation interventions on U.S. Indian reservations

Abstract: To what extent do differential levels of investment in public health inputs explain observed differences in health outcomes across socioeconomic and racial groups? This study investigates the impact of 3,700 projects that were part of a widespread Federal initiative to improve sanitation infrastructure on U.S. Indian reservations starting in 1960. Sanitation investment substantially reduced the cost of clean water for households, leading to sharp reductions in both waterborne gastrointestinal disease and infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 21 publications
5
78
0
4
Order By: Relevance
“…Cutler and Miller (2005) show an effect of adoption of clean water technology in U.S. cities on mortality rates in the twentieth century. Watson (2006) documents an effect of improving sanitation in U.S. Native American populations on infant mortality.…”
Section: Outlinementioning
confidence: 99%
“…Cutler and Miller (2005) show an effect of adoption of clean water technology in U.S. cities on mortality rates in the twentieth century. Watson (2006) documents an effect of improving sanitation in U.S. Native American populations on infant mortality.…”
Section: Outlinementioning
confidence: 99%
“…Poor sanitation can also spread parasitic infections, which are rarely fatal by themselves but contribute to poor health and poor physical growth (Haque 2007). 4 Several studies in economics have also identified important effects of sanitation-related diseases on anemia and early-life mortality (e.g., Coffey et al Forthcoming;Cutler and Miller 2005;Galiani et al 2005;Watson 2006) as well as effects on subsequent human capital accumulation (e.g., Baird et al 2016;Bleakley 2007;Hammer and Spears 2016;Spears and Lamba 2016).…”
Section: Background: Population Density Sanitation and Disease Extementioning
confidence: 99%
“…In a rural setting, Watson (2006) exploits the fact that a series of water and sanitation interventions introduced on Native American reservations in the United States during 1960-1998 were likely uncorrelated with other factors affecting infant health and plausibly exogenous to local community characteristics after accounting for county and year fixed effects. This research suggests that a 10 percent increase in the fraction of homes with improved water and sanitation services reduced infant mortality by 4 percent.…”
Section: Piped Water and Sanitationmentioning
confidence: 99%
“…In the United States, these interventions were jointly responsible for most of the rapid decline in the child mortality rate in the early 20th century (Cutler and Miller 2005), and more recently for substantial health improvements on Native American reservations (Watson 2006). For this class of interventions, a key outstanding question is what institutional arrangements can best support investment in infrastructure and its maintenance.…”
mentioning
confidence: 99%